READING AND WRITING LEARNING GUIDANCE FOR CHILDREN WITH THE ANAK HEBAT (AHE) METHOD AT ANAK HEBAT LEARNING CENTER, BENGKULU CITY - Ulfa, Fadillah; Kustati, Martin; Amelia, Rezki; Gusmirawati, Gusmirawati (Jurnal Inovasi dan Terapan Pengabdian Masyarakat, 2024)
This community service aims to improve basic literacy skills in early childhood children at the Anak Hebat Learning Center Unit 8169 through the implementation of the Anak Hebat (AHE) method. This program is designed to help children aged 4.5 to 8 years master reading and writing skills effectively with an interactive and enjoyable approach. The method used is Asset-Based Community Development (ABCD), which consists of several main steps: asset identification, parent involvement, program implementation, method development and evaluation, as well as program evaluation.. The AHE method combines various activities such as brain gymnastics, tiered module-based learning, writing practice, and educational games. Evaluations were conducted to measure the reading and writing abilities of participants before and after the implementation of the community service, using achievement cards. The results showed an improvement in children's literacy skills, especially in mastering basic letters and words. This community service has a positive impact on improving basic literacy, by empowering parents and teachers to play an active role in the learning process.